Everybody knows English? Language use in the world of learning - Varantola, Krista (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
This article will focus on the use of English as a global means of communication in higher education (HE) and research. The use of English is taken for granted as a global means of communication in the academic world. Therefore language issues are rarely problematized in science-policy contexts. This article will try to make the language issue visible by addressing aspects of a use of a lingua franca from a historical and pragmatic perspective and discuss its effects on everyday university life in non-English-speaking countries.